Split-plot designs: discussion and examples. (1st October 2010) - Ledolter, Johannes
Split-plot designs and the appropriate statistical analysis of the resulting data are frequently misunderstood by industrial experimenters. The objective of this tutorial paper is to review split-plot designs for full and fractional factorial experiments, explain why they often arise in industrial experiments, and provide several illustrative examples.